Comunidad virtual en Salud Pública. Participación y pertenencia - Pérez, Alejandra Beatriz (2023)
Fil: Pérez, Alejandra Beatriz. Universidad de Buenos Aires. Secretaría de Asuntos Académicos. Buenos Aires, Argentina